The role of Sawarna Tourism Village in supporting the Bayah Dome Geopark in Lebak Regency - Hilmi Mubarok; Forina Lestari; Dedi Nugraha (Universitas Merdeka Malang, 2023)
Tourism villages are currently one of the potentials being encouraged in Indonesia. On the other hand, the geopark development that the government has rolled out also holds three pillars: conservation, education, and community development, one of which is tourism. Sawarna Village has a distinctive attraction in the form of the physical uniqueness of the rural natural environment, the natural wealth of tourist charms, and the social life of its people, which are packaged naturally and attractively. In developing tourism in Sawarna Village, some problems hinder the implementation of tourism development, including a lack of facilities and infrastructure at tourist sites, lack of coordination between Sawarna Village Managers and Regional Governments, not yet optimal empowerment for community-based tourism managers, lack of opportunities for the local community village of Sawarna to market their handicrafts and culinary products at tourist sites. This study analyzes the alternative strategy for tourism development in Sawarna Village. The method used in this research is descriptive qualitative. This study uses SWOT analysis to describe the potential problems in Sawarna Village and to determine alternative strategies. The results showed that the strategy to be implemented in developing Tourism in Sawarna Village was to improve the quality of tourism infrastructure facilities and increase tourist attractions such as the Sawarna Beach tourism object such as Legon Pari Beach, Pulo Manuk Beach, Karang Bokor Beach.